LOCUS OF CONTROL AS DETERMINANTS OF ONLINE - DATING BEHAVIOUR AMONG GRADUATES IN KWARA - STATE - Islamiyyah Olajire Ibraheem; Mary O Esere (OPTIMA: Journal Of Guidance and Counseling, 2024)
This study investigated locus of control as determinant of online dating among university students in Kwara State. Descriptive survey design with correlational approach was adopted. 380 university students from four universities in Kwara State were the respondents of the study. Instruments for data collection were Online Dating Behaviour Scale adapted from Tinsel (2019) Survey and locus of control scale adapted from Rotter (1966). Three null hypotheses were generated and tested at .05 alpha levels. Pearson Product Moment Correlation was used. Result showed a significant relationship between online dating and internal locus of control of university students in Kwara State (r. calculated = 0.41, df = 378 and p 0.05); a significant relationship between online dating and powerful others locus of control of university students in Kwara State (r. calculated = -0.62, df = 378 and p 0.05); a significant relationship between online dating and chance locus of control of university students in Kwara State (r. calculated = -0.26, df = 378 and p 0.05). Recommendations based on the finding of the study were proffered.